Evolution of an Examination: M.R.C.P. (U.K.). Issue 5910 (13th April 1974) - Fleming, P. R.; Manderson, W. G.; Matthews, M. B.; Sanderson, P. H.; Stokes, J. F.
Abstract : Recent changes in the structure of the examination for M.R.C.P. (U.K.) have prompted a review of these together with a historical outline of the examinations which preceded it at the Royal Colleges of Physicians of Edinburgh, Glasgow, and London. Part I of the examination continues to fulfil its role as a screen and a slight change in the marking system appears to have improved its discriminating powers still further. The major change in part II is the substitution of a more objective written test in place of the essay papers.